The influences of tourists' emotions on the selection of electronic word of mouth platforms. (June 2018) - Yan, Qiang; Zhou, Simin; Wu, Sipeng
Abstract: The overall purpose of this study is to explore the relationship between emotion tendency and e-WOM publishing during four phases of tourists' travel experience, from the multiplatform perspective, which has not been much studied in the field of tourism management. We firstly carried out a sentiment analysis of reviews on two platforms, the results indicated that there is a ∖ distinct emotion polarity. Then we measured 260 Chinese respondents' emotion tendency in four scenes using mDES and investigated their selection of different platforms to publish e-WOM. The statistical analysis and correlation analysis revealed that tourists with positive affect tend to share their experiences on social media while those with negative affect prefer integrated tourism websites. The results also revealed that the positive emotions are more frequent than negative emotions in a journey and the emotions of males and females are quite different. Finally, we give some management suggestions to different platforms. Highlights: The emotion polarity in different platforms (Sina andDianping.com ) are quite different. Tourists with positive affect tend to share their experiences on social media. Tourists with negative affect tend to comment on integrated tourism websites. The tourists are positive in a journey and the emotions between different groups are different.